BARRIERS TO INCLUSIVE PLAY IN EARLY CHILDHOOD EDUCATION; PERSPECTIVES FROM TEACHERS AND PARENTS OF CHILDREN WITH DEVELOPMENTAL DISABILITIES - Muwafiq Ibrahim Mas'ud (PEDAGOGIK : JURNAL PENDIDIKAN, 2024)
This research aims to examine the understand of the transformation of the educational paradigm towards the inclusion of play for children with developmental disabilities, especially dyslexia, dysgraphia, and dyscalculia, in the context of early childhood education. This study uses a qualitative approach to explore how changes in inclusive teaching methodology affect the engagement and development of children with these disabilities. Data was collected through in-depth interviews with educators and parents and direct observation in classroom settings. Research findings show that implementing inclusive teaching methods significantly increases the active participation of children with dyslexia, dysgraphia, and dyscalculia, as well as their social skills. This intervention also positively impacted children's cognitive and emotional development, with essential contributions from family support and an adaptive learning environment. This research provides new insight into the importance of inclusive methodologies in supporting children with developmental disabilities. It emphasizes the need for collaboration between educators, families, and service providers to create more adaptive and supportive learning environments.